State of the Climate in Latin America and the Caribbean 2024 - World Meteorological Organization (United Nations, 2025)
The WMO State of the Climate in Latin America and the Caribbean 2024, is the fifth edition of climate reports published annually for this region and has involved National Meteorological and Hydrological Services (NMHSs), WMO Regional Climate Centres (RCCs), and several research institutions, as well as United Nations agencies, international and regional organizations. The report provides the status of key climate indicators and latest data and information on impacts, risks and policy from United Nations agencies. It addresses specific physical science, socio-economic and policy aspects that are relevant to LAC and responds to Members needs in the fields of climate monitoring, climate change and climate services.